Dissolution of marine shales and its influence on reservoir properties in the Jiaoshiba area, Sichuan Basin, China. (April 2019) - Wang, Hu; He, Zhiliang; Zhang, Yonggui; Bao, Hanyong; Su, Kun; Shu, Zhiheng; Zhao, Conghui; Wang, Ruyue; Wang, Tao
Abstract: The dissolution of marine shales and its influence on reservoir physical properties was revealed based on shale samples from the Ordovician-Silurian Wufeng and Longmaxi Formations in the southeast of the Sichuan Basin, China. Three kinds of gas storage spaces were formed by dissolution, including intergranular dissolution (InterD) pores, intragranular dissolution (IntraD) pores and dissolution microfractures (DmF). The diameters of the InterD and IntraD are 10.2–72.4 μm and 0.13–1.52 μm, respectively. The apertures of the DmF are between 0.5 and 11.2 μm. The dissolution effect resulted in a diagenetic environment for quartz cementation and a material basis for calcite veins. The main controlling factors of the dissolution effect are the mineral constituent content in the matrix, the amount of organic matter and the strata burial rate. Dissolution pores and fractures play important roles in shale gas enrichment and migration. The porosity of shale reservoirs with DmF is twice the porosity of reservoirs without DmF, and the spaces formed by dissolution pores and fractures are well connected. A new model for shale gas flow in shale reservoirs was proposed, which provides a new understanding for the connection between organic material pores, and the results can be used for shale reservoirs worldwide. Highlights: Calcite veins are effective channels for shale flow. Dissolution pores and dissolution fractures play an important role in the transfusion of shale gas. Three main controlling factors of dissolution in shale reservoirs are given. A new model for shale gas flow in shale reservoirs is proposed.